2013
DOI: 10.1097/scs.0b013e31828f2910
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary Sinusitis After Sinus Lift Due to Gemella morbillorum

Abstract: Sinus lift is a predictable procedure for increasing alveolar bone height in the posterosuperior alveolar regions to allow oral prosthetic rehabilitation. Several complications have been documented in the literature and vary from sinus membrane perforation to maxillary rhinosinusitis. The authors present a case of Gemella morbillorum acute sinusitis after sinus lift surgery. The purpose of this report is to describe the surgical and pharmacological management of a patient allergic to penicillin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…It should be noted that, in addition to amoxicillin/clavulanate 1,4,7 and doxycycline, 38 practitioners have used perioperative amoxicillin, 2,3,36-38 clindamycin, 2,3,7,12,16 cephalosporins, 1,6,11 metronidazole, 12,16 tetracycline, 12,38 clarithromycin, 10 and levofloxacin 10 for SES or as treatment for postoperative sinus graft infection. For SES, perioperative antibiotics have been delivered locally, 3,16,38 orally, [1][2][3][4]6,7,[10][11][12]16,[36][37][38] or intravenously. 4,6,7,10 Although direct evidence to validate amoxicillin/clavulanate and doxycycline as optimal medications for antibiotic prophylaxis before SES does not exist, these agents are justified in the setting of SES based on established principles of anti-infective therapy, available data on the target microbial profile, and target bacteria antibiotic susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It should be noted that, in addition to amoxicillin/clavulanate 1,4,7 and doxycycline, 38 practitioners have used perioperative amoxicillin, 2,3,36-38 clindamycin, 2,3,7,12,16 cephalosporins, 1,6,11 metronidazole, 12,16 tetracycline, 12,38 clarithromycin, 10 and levofloxacin 10 for SES or as treatment for postoperative sinus graft infection. For SES, perioperative antibiotics have been delivered locally, 3,16,38 orally, [1][2][3][4]6,7,[10][11][12]16,[36][37][38] or intravenously. 4,6,7,10 Although direct evidence to validate amoxicillin/clavulanate and doxycycline as optimal medications for antibiotic prophylaxis before SES does not exist, these agents are justified in the setting of SES based on established principles of anti-infective therapy, available data on the target microbial profile, and target bacteria antibiotic susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…5,8,[17][18][19][20][21][22][23][24][25][26][27][30][31][32][33][34][35] Studies that merely reported use of perioperative antibiotics for SES or associated postsurgical complications were excluded, as these reports neither provided rationale for antibiotic selection nor sought to specifically justify use of one antibiotic over another. [1][2][3][4]6,7,[10][11][12]14,16,[36][37][38]…”
Section: Search Outcomementioning
confidence: 99%
See 3 more Smart Citations